2017
DOI: 10.1038/s41536-017-0023-2
|View full text |Cite
|
Sign up to set email alerts
|

Biomaterial-driven in situ cardiovascular tissue engineering—a multi-disciplinary perspective

Abstract: There is a persistent and growing clinical need for readily-available substitutes for heart valves and small-diameter blood vessels. In situ tissue engineering is emerging as a disruptive new technology, providing ready-to-use biodegradable, cell-free constructs which are designed to induce regeneration upon implantation, directly in the functional site. The induced regenerative process hinges around the host response to the implanted biomaterial and the interplay between immune cells, stem/progenitor cell and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
226
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(230 citation statements)
references
References 226 publications
2
226
1
1
Order By: Relevance
“…One possible approach to repair the tissue in all its components is to provide an exogenous matrix as an ideal substrate and support for cell transplantation. Several biomaterials, either natural or synthetic, have been used as ECM substitutes thus far . Undoubtedly, collagen, gelatin, alginate, and fibrin are the most used among natural polymers, as they are naturally charged with numerous cell binding sites while ensuring high biocompatibility and biodegradability.…”
Section: Regenerating the Myocardium By The “Right” Matrixmentioning
confidence: 99%
“…One possible approach to repair the tissue in all its components is to provide an exogenous matrix as an ideal substrate and support for cell transplantation. Several biomaterials, either natural or synthetic, have been used as ECM substitutes thus far . Undoubtedly, collagen, gelatin, alginate, and fibrin are the most used among natural polymers, as they are naturally charged with numerous cell binding sites while ensuring high biocompatibility and biodegradability.…”
Section: Regenerating the Myocardium By The “Right” Matrixmentioning
confidence: 99%
“…Blending of polyurethane by natural biological polymer like gelatin is followed by two aims: (1) increment of biological properties of composite scaffolds especially for cell adhesion and proliferation, (2) adjusting biodegradation rate of the scaffolds to help effective formation of neo tissue (Baheiraei et al, ; Wissing, Bonito, Bouten, & Smits, ).…”
Section: Introductionmentioning
confidence: 99%
“…This approach takes advantage of the surrounding biological microenvironment, directing the fate of cells to regenerate new tissue without complicated prior in vitro cell manipulation . Several reviews can be found in the literature describing what is currently known about the mechanisms and strategies used to induce in situ cell differentiation and tissue regeneration (Chen et al, 2011;Yang et al, 2014;Talacua et al, 2015;Dhand et al, 2016;Murdock and Stephen, 2017;Wissing et al, 2017).…”
Section: Introductionmentioning
confidence: 99%